Belâgat İlmi Açısından Süyûtî’nin Kur’an’a Yaklaşımı - Çaharbağlı, Abdusalam (İstanbul Sabahattin Zaim Üniversitesi, 2025)
The Qur’ān, with its eloquent structure and profound semantic layers, has consistently occupied a central place in Islamic scholarship. Among the disciplines that emerged to facilitate a deeper understanding of its divine message, Arabic rhetoric (balāgha) holds a particularly significant position, especially in relation to the doctrine of iʿjāz (inimitability). This study explores the role of balāgha in the Qur’ānic exegesis of Jalāl al-Dīn al-Suyūṭī, one of the most prolific scholars of the classical Islamic tradition. Drawing primarily on his two key Works-al-Itqān fī ʿUlūm al-Qurʾān and al-Durr al-Manthūr-the research examines al-Suyūṭī’s interpretive strategies regarding rhetorical figures such as metaphor, simile, and metonymy, while also assessing how he employed classical rhetorical theories to explicate Qur’ānic passages. The findings suggest that al-Suyūṭī not only inherited the classical rhetorical legacy but also developed a systematic and text-centered method that contributed to the consolidation of balāgha as a vital exegetical tool in Qur’ānic studies.

Kur’ân-ı Kerîm’in nazmı yapısı ile içerdiği manevî derinlik, nüzulünden itibaren İslâm ilim geleneğinde çok yönlü yorumlara konu olmuş; bu yönüyle Kur’ân, hem dilsel hem de teolojik bir çözümleme nesnesi hâline gelmiştir. Kur’ân’ın bu çok katmanlı yapısını anlamada en işlevsel ilim dallarından biri şüphesiz belâgattır. Zira belâgat, lafzın mana ile kurduğu estetik ilişkiyi ortaya koyarak, i‘câzın dilsel boyutuna dair önemli ipuçları sunmaktadır. Bu bağlamda elinizdeki çalışma, Celâleddîn es-Süyûtî’nin Kur’ân’a yaklaşımında belâgat ilmine nasıl yer verdiğini tespit etmeyi hedeflemektedir. Araştırma, müellifin el-İtkān fî ‘ulûmi’l-Kur’ân ve ed-Dürrü’l-mensûr fî’t-tefsîr bi’l-Me’sûr adlı eserleri çerçevesinde şekillenmiş; mecâz, istiâre, teşbîh gibi belâgat unsurlarının söz konusu eserlerdeki yansımaları, teorik ve pratik düzlemde analiz edilmiştir. Elde edilen bulgular, Süyûtî’nin klasik belâgat mirasını sistematik biçimde yorumladığını ve bunu metin merkezli bir yöntemle Kur’ân ayetlerine tatbik ettiğini ortaya koymaktadır.
Süyûtî's Approach to the Qur'an from the Perspective of Rhetoric
Keywords: al-Suyūṭī; Rhetoric; I‘jāz; Qur’an; Tafsīr; al-Itqān; al-Durr al-Manthūr; Metaphor; Stylistics; Balāgha; Süyûtî; Belâgat; İ‘câz; Kur’ân; Tefsir; el-İtkān; ed-Dürrü’l-Mensûr; Mecâz; İstiâre; Beyân